THE ROBBERY MADE BY USING TOOLS WITH A PURPOSE TO BREAK VICTIM‘S WILL - Žukovaitė, Inga (Teisė, 2016)
This article examines a group of characteristics qualifying a robbery which is very relevant in practice. This group of characteristics is related to tools which are being used during a robbery with a purpose to break victim‘s will. According to Lithuanian Criminal Code, these tools are a knife, an object especially designed to hurt a person, firearm and non firearm weapons. This topic is studied at both theoretical and practical level. The light is shed on gaps and inaccuracies of juridical regulation in Lithuanian Criminal Code, with some suggestions of how to improve juridical consolidation for this group of characteristics qualifying a robbery. The results show that tools can be used both the direct and indirect way. The gaps of regulation are related to the fact that the grouping of tools does not have sufficiently clear criteria to distinguish both because the regulation is composed by naming general and individual items. The characteristic of using an object especially designed to hurt a person includes the characteristic of using knife. The definition of characteristic of using an object especially designed to hurt a person is misleading because the content of this characteristic is related not to prior adaptability, but the way to use item during the robbery. The interpretation of firearms should not be limited formal definitions of law of arm control or technical evaluation of weapons data made by experts.